Neuroprotective synergy of curcumin and Glycyrrhiza glabra in an alzheimer’s model: implications for inflammation and redox pathways - Liu, Shanshan; Yan, Jing; Dong, Jian (Frontiers in Pharmacology, 2025)
ObjectivesAlzheimer’s disease (AD) is a progressive neurodegenerative disorder marked by cognitive impairment, amyloid-beta (Aβ) accumulation, tau hyperphosphorylation, and chronic neuroinflammation. Despite symptomatic treatments, no current therapies halt disease progression. Traditional Chinese Medicine (TCM) offers potential multi-targeted interventions in complex diseases like AD. In this study, we evaluated the individual and combined neuroprotective effects of curcumin and Glycyrrhiza glabra in a D-galactose sodium nitrite-induced mouse model of AD. Behavioral analysis, biochemical assays, and molecular profiling were conducted to assess cognitive function, inflammatory cytokine expression, oxidative stress, and AD-related protein levels.MethodsMice were randomly assigned to five groups: control, AD model, curcumin-treated, Glycyrrhiza glabra-treated, and combination-treated groups. Cognitive function was assessed using the Morris water maze. Levels of neuroinflammatory cytokines interleukin-6(IL-6) and tumor necrosis factor-alpha (TNF-α), AD-related proteins amyloid precursor protein (APP) and microtubule-associated protein tau (MAPT),oxidative stress (MDA), and antioxidant capacity (SOD) were evaluated via quantitative PCR and Western blotting.ResultsCurcumin alone modestly improved spatial learning and reduced IL-6 (p < 0.05), whereas Glycyrrhiza glabra had limited effects. The combination therapy yielded the strongest outcomes, significantly reducing escape latency (p < 0.01), IL-6 and TNF-α levels (p < 0.01 and p < 0.05), and downregulating APP and MAPT expression. Additionally, oxidative damage was attenuated, as indicated by decreased MDA and elevated SOD activity (p < 0.001). Although direct measurement of TLR4/NF-κB phosphorylation was not performed, the observed anti-inflammatory and antioxidant effects suggest possible modulation of this pathway.ConclusionCo-administration of curcumin and Glycyrrhiza glabra exerts synergistic neuroprotective effects by attenuating neuroinflammation, oxidative stress, and AD-related protein expression, surpassing monotherapy outcomes. These findings suggest a synergistic neuroprotective mechanism via modulation of TLR4/MyD88/NF-κB and redox pathways. This study provides preclinical evidence supporting the development of TCM-based combination strategies for AD intervention.